Knowledge, attitudes, and practices of pregnant women regarding fetal growth restriction: a cross-sectional study - Yanfei Zhu; Chenyang Ding; Lili Fang; Zhuchun Mei; Xiaoe Xie (Frontiers in Public Health)
ObjectiveTo investigate the knowledge, attitudes, and practices (KAP) of pregnant women regarding fetal growth restriction (FGR).MethodsThis cross-sectional study was conducted from December 2024 to January 2025 in Lishui City, Zhejiang Province, with pregnant women as study participants. A self-administered questionnaire was used to collect demographic information and assess KAP scores.ResultsA total of 381 participants were included in the study. The majority were <30 years old (55.12%), pregnant for >32 weeks (56.17%), and with their first pregnancy (48.56%). The mean scores for knowledge, attitudes, and practices were 11.08 ± 5.44 (out of 22, 50.36%), 30.33 ± 3.07 (out of 40, 75.83%), and 37.72 ± 2.99 (out of 40, 94.30%), respectively. Knowledge scores were positively correlated with attitude (r = 0.1269, p = 0.0132) and practice (r = 0.2838, p < 0.001) scores. The attitude scores were correlated with the practice scores (r = 0.2140, p < 0.001). Structural equation modeling (SEM) revealed that knowledge had direct influences on attitudes (β = 0.17, p < 0.001) and practices (β = 0.11, p = 0.004). Attitudes had a direct influence on practices (β = 0.61, p < 0.001). Knowledge had an indirect influence on practices through attitudes (β = 0.10, p < 0.001).ConclusionPregnant women exhibited limited knowledge but demonstrated favorable attitudes and proactive practices regarding FGR. Improving the knowledge about FGR through educational interventions could enhance both attitudes and practices.